2019
DOI: 10.1038/s41598-019-46166-z
|View full text |Cite
|
Sign up to set email alerts
|

Silent Changes in Sleep Quality Following Mandibular Setback Surgery in Patients with Skeletal Class III Malocclusion: A Prospective Study

Abstract: Mandibular setback surgery (MSS) for skeletal class III patients can result in a relative reduction of pharyngeal airway space (PAS). Consequently, there is a possibility of the decline of sleep quality after surgery. We investigated changes in sleep quality measured by overnight polysomnography (PSG) and the three-dimensional (3D) volumes of PAS following MSS with or without Le Fort I osteotomy (LF I) in class III patients (N = 53). Overnight PSG and cone beam computed tomography were conducted at preoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…Other studies reported worsening of sleep quality or the occurrence of sleep apnea after mandibular setback surgery in subjects with no signs or symptoms of airway obstruction before the operation [24,25]. The present findings also corroborate the results of some studies [26][27][28] that indicated narrowing of the pharyngeal airway was less in subjects treated with 2-jaw orthognathic surgery than mandibular sagittal compression alone. The widening of the pharyngeal airway after maxillary advancement has also been reported in previous investigations [28][29][30], implying reduced airway resistance and improved breathing.…”
Section: T1-t0supporting
confidence: 90%
“…Other studies reported worsening of sleep quality or the occurrence of sleep apnea after mandibular setback surgery in subjects with no signs or symptoms of airway obstruction before the operation [24,25]. The present findings also corroborate the results of some studies [26][27][28] that indicated narrowing of the pharyngeal airway was less in subjects treated with 2-jaw orthognathic surgery than mandibular sagittal compression alone. The widening of the pharyngeal airway after maxillary advancement has also been reported in previous investigations [28][29][30], implying reduced airway resistance and improved breathing.…”
Section: T1-t0supporting
confidence: 90%
“…According to this meta-analysis, there has been no statistically significant increase in sleep apnea risk before and after surgery. A three-dimensional (3D) PAS volume showed a significant decrease in the oropharyngeal airway, and no significant change has been observed in the sleep symptoms [8]. Reports indicated that bimaxillary orthognathic surgery to reduce PAS played a role, but it does not increase AHI, one of the important determinants of sleep apnea [18,19,21,23].…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic changes in airway anatomy may also contribute to obstructive sleep apnea [8]. The mandibular setback surgery (MdS) effect on the association of the soft tissue and skeletal tissue has been also demonstrated that could result in a relative reduction of the pharyngeal airway space [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…For patients with severe mandibular prognathism or patients with potential for OSA development, two-jaw surgery should be strongly considered [34]. In addition, a study reported that although there are no subjective symptoms after mandibular setback with or without maxillary surgery, objective sleep quality determined by polysomnography may be decreased [5]. However, a short-term observation period (3 months) needs to be considered in this previous study.…”
Section: Significant Airway Reduction After Mandibular Setback Surgerymentioning
confidence: 99%
“…In addition, a recent study reported that among 12 patients with a mandibular setback exceeding 10 mm, 4 patients developed postoperative OSA, and the apnea-hypopnea index (AHI) was slightly increased significantly after the surgery [4]. Another study found that although subjective symptoms were not exacerbated, objective sleep quality was decreased after mandibular setback surgery [5]. When mandibular setback was performed with maxillary advancement or posterior impaction, the pharyngeal airway volume significantly decreased.…”
Section: Introductionmentioning
confidence: 99%